RET mutational spectrum in Hirschsprung disease: evaluation of 601 Chinese patients. - Man-Ting So; Thomas Yuk-Yu Leon; Guo Cheng; Clara Sze-Man Tang; Xiao-Ping Miao; Belinda K Cornes; Ngoc Ngo Diem; Long Cui; Elly Sau-Wai Ngan; Vincent Chai-Hang Lui; Xuan-Zhao Wu; Bin Wang; et al. (PLoS ONE, 2011)
Rare (RVs) and common variants of the RET gene contribute to Hirschsprung disease (HSCR; congenital aganglionosis). While RET common variants are strongly associated with the commonest manifestation of the disease (males; short-segment aganglionosis; sporadic), rare coding sequence (CDS) variants are more frequently found in the lesser common and more severe forms of the disease (females; long/total colonic aganglionosis; familial).Here we present the screening for RVs in the RET CDS and intron/exon boundaries of 601 Chinese HSCR patients, the largest number of patients ever reported. We identified 61 different heterozygous RVs (50 novel) distributed among 100 patients (16.64%). Those include 14 silent, 29 missense, 5 nonsense, 4 frame-shifts, and one in-frame amino-acid deletion in the CDS, two splice-site deletions, 4 nucleotide substitutions and a 22-bp deletion in the intron/exon boundaries and 1 single-nucleotide substitution in the 5' untranslated region. Exonic variants were mainly clustered in RET the extracellular domain. RET RVs were more frequent among patients with the most severe phenotype (24% vs. 15% in short-HSCR). Phasing RVs with the RET HSCR-associated haplotype suggests that RVs do not underlie the undisputable association of RET common variants with HSCR. None of the variants were found in 250 Chinese controls.